Studies in Greek epigraphy and history in honor of Stefen V. - Gary Reger (Ausonius Éditions, 2010)
This collection of studies in Greek epigraphy honors the work of Stephen V. Tracy. His meticulous research on the hands of Attic letter-cutters has transformed the way we think about Greek inscriptions in Attica and beyond. The twenty-nine scholars who have contributed to this volume offer papers ranging from publication of new inscriptions and studies of others long-known to wide-ranging discussions of historical, religious, and social matters. Chronologically and geographically they cover Greece, the Aegean, and western Asia Minor from the Archaic period to the Roman Empire. What unites the work here offered to Tracy is the centrality of epigraphy to the questions addressed and conviction that careful attention to even the smallest details of the epigraphic evidence can advance our understanding of the Greek past in rich and unexpected ways.